E-learning Globalization : the impact of E-learning - what difference has it made. - Skinner, Heather (Education + Training: Volume 56, Issue 2/3., 2014)
The ubiquity of information and communication technology in the past two decades or so, and the more recent growth in the use of mobile wireless devices, has transformed various aspects of daily life for many people worldwide. It is therefore unsurprising that such technologies would also find their way into transforming various aspects of education and training. What may be surprising is that, even though forms of computer assisted learning have been used for over 40 years, educators and trainers can still find themselves grappling with relatively basic issues of defining the way this transfo.